Pengaruh Keteladanan Guru Dan Budaya Sekolah Islami Terhadap Perilaku Moral Siswi SMA IT Nurul Ilmi Siak - Sumardi; Muhammad Ghufron; Dadang Falah Mutaqin; Muhammad Alfi Syahrin (Education Research Center, 2026)
This study aims to analyze the influence of teacher role modeling and Islamic school culture on students’ moral behavior at SMA IT Nurul Ilmi Siak. A quantitative correlational design was applied. Data were collected through questionnaires distributed to 62 respondents. Multiple regression analysis was conducted to examine the research hypotheses. The results revealed that teacher role modeling significantly influenced moral behavior (p = 0.050) and Islamic school culture also significantly influenced moral behavior (p < 0.001). Simultaneously, both variables significantly affected moral behavior (F = 20.62; p = 0.000). The coefficient of determination (R² = 0.411) indicates that 41.1% of the variation in moral behavior can be explained by teacher role modeling and Islamic school culture. This study highlights the importance of Islamic educational culture and exemplary guidance in shaping students’ moral development.